Using cloud technologies in the teaching of higher mathematics - M. A. Kyslova (Academy of Cognitive and Natural Sciences, 2013)
Today, cloud technology is growing in popularity in various areas of human activity. Cloud technology is providing the user with the ability to use programs, services, and disk space remotely via the Internet. All this significantly simplifies human life and does not overload a home computer or a mobile device with excessive heavy information. The use of cloud technologies in education significantly reduces the demands on the resources of personal computers.